Hyperglycemia-induced cerebral hematoma expansion is mediated by plasma kallikrein - Liu, Jia; Gao, Ben-Bo; Clermont, Allen C; Blair, Price; Chilcote, Tamie J; Sinha, Sukanto; Flaumenhaft, Robert; Feener, Edward P (Nature medicine, 2011)
Intracerebral hemorrhage, a common cause of stroke, has more dire consequences in diabetics than in nondiabetics. Using experimental rodent models, Jia Liu et al . find that the deleterious effects of diabetes on intracerebral hemorrhage may be due to the action of the protein plasma kallikrein, discovered to directly inhibit platelet aggregation through an osmolarity-sensitive mechanism. Hyperglycemia is associated with greater hematoma expansion and poor clinical outcomes after intracerebral hemorrhage. We show that cerebral hematoma expansion triggered by intracerebral infusion of autologous blood is greater in diabetic rats and mice compared to nondiabetic controls and that this augmented expansion is ameliorated by plasma kallikrein (PK) inhibition or deficiency. Intracerebral injection of purified PK augmented hematoma expansion in both diabetic and acutely hyperglycemic rats, whereas injection of bradykinin, plasmin or tissue plasminogen activator did not elicit such a response. This response, which occurs rapidly, was prevented by co-injection of the glycoprotein VI agonist convulxin and was mimicked by glycoprotein VI inhibition or deficiency, implicating an effect of PK on inhibiting platelet aggregation. We show that PK inhibits collagen-induced platelet aggregation by binding collagen, a response enhanced by elevated glucose concentrations. The effect of hyperglycemia on hematoma expansion and PK-mediated inhibition of platelet aggregation could be mimicked by infusing mannitol. These findings suggest that hyperglycemia auguments cerebral hematoma expansion by PK-mediated osmotic-sensitive inhibition of hemostasis.